Pengaruh Penambahan Tepung Kedelai Terhadap Cita Rasa Dan Kadar Air Cookies Ubi Jalar Ungu - I Ketut Swirya Jaya (Jurnal Gizi Prima (Prime Nutrition Journal), 2019)
Background: KEK is a condition of expectant and WUS (women of fertile age) lack of energy and protein that goes chronic. In NTB, women of reproductive age who consume energy below the minimum requirement is 46.2% and the protein below the minimum requirement is 34.3%. Cookies are snacks that have been known and in demand all age groups. Now, cookies have a lot of a mixture of raw materials with a variety of objectives which is to improve the nutritional value. One of these are  purple sweet potato cookies with soy flour complementation as a form of development of food products that contain enough energy and protein. Objective: To know the organoleptic and water content of purple sweet potato cookies with soy flour complementation. Methods: Design experiment use completely randomized design (CRD), which consists of five treatment soy flour complementation are 10%, 15%, 20%, 25% and 30% with three replications. Data organoleptic and water content was analyzed using SPSS that is Analysis of Variance (One Way ANOVA) was continued by Turkey’s test. Results: Soy flour did not affect the color and texture of purple sweet potato cookies (p> 0.05), but affect the smell and taste (p <0.05). Purple sweet potato cookies with t3 treated (20%) have the most preferred taste. Soy flour on purple sweet potato cookies did not affect the moisture content of purple sweet potato cookies (p> 0.05).                                                                                                 Conclusion: Soy flour did not affect the color and texture of purple sweet potato cookies, but affect the smell and taste of purple sweet potato cookies. Soy flour on purple sweet potato cookies did not affect the water content of purple sweet potato cookies.